Acetabular denervation and pectinectomy in the treatment of canine coxofemoral dysplasia: Case report - SILVA, CATARINA RAFAELA (Pubvet, 2020)
Coxofemoral dysplasia (DCF) is an orthopedic condition characterized by the abnormal development of the hip joint and consequent degeneration of the articular components. The clinical signs when discrete are little evidenced by the tutors and their manifestation varies according to the age of the animal. The diagnosis is made through anamnesis, physical and radiographic findings. The treatment is performed with the intention of relieving pain and preventing the progression of degenerative joint disease. The present study aims to report the technique of acetabular denervation and pectineotomy as treatment of hip dysplasia in canine, where it can be observed a significant clinical evolution in the postoperative period of the animal.